2006
DOI: 10.1117/12.639933
|View full text |Cite
|
Sign up to set email alerts
|

Matrix embedding for large payloads

Abstract: Abstract-Matrix embedding is a previously introduced coding method that is used in steganography to improve the embedding efficiency (increase the number of bits embedded per embedding change). Higher embedding efficiency translates into better steganographic security. This gain is more important for long messages than for shorter ones because longer messages are in general easier to detect. In this paper, we present two new approaches to matrix embedding for large payloads suitable for practical steganographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 7 publications
0
117
0
1
Order By: Relevance
“…It can be seen from the table that both OutGuess and StegHide are almost completely detectable (especially when using PF-23, PF-274, and DCT-hist features), but YASS is not detectable at equivalent hiding rates. We also experimented with the F5 steganographic scheme [5], which uses matrix embedding (see for example [27]), and found that this scheme is also undetectable at equivalent embedding rates using PF-274 and PF-23 features. Matrix embedding allows hiding at embedding efficiencies (defined as number of bits hidden for every change made to the host symbols), potentially much higher than the trivial efficiency of 2 bits per change (bpc).…”
Section: Comparison With Competing Methodsmentioning
confidence: 99%
“…It can be seen from the table that both OutGuess and StegHide are almost completely detectable (especially when using PF-23, PF-274, and DCT-hist features), but YASS is not detectable at equivalent hiding rates. We also experimented with the F5 steganographic scheme [5], which uses matrix embedding (see for example [27]), and found that this scheme is also undetectable at equivalent embedding rates using PF-274 and PF-23 features. Matrix embedding allows hiding at embedding efficiencies (defined as number of bits hidden for every change made to the host symbols), potentially much higher than the trivial efficiency of 2 bits per change (bpc).…”
Section: Comparison With Competing Methodsmentioning
confidence: 99%
“…Second, we model how LSB replacement converts trace subsets in the cover to trace subsets in a stego image, depending on the size of payload. We suppose that the LSB of each sample is flipped, independently, with probability p 2 -this corresponds to embedding a payload (uncorrelated with the cover) of length pN by randomized LSB replacement, or perhaps the embedding of a longer payload when LSB flipping is used as part of a source coding scheme [14] (of course the estimator will be truly for twice the number of flipped pixels, regardless of the connection this has with payload size; it could be nothing else). Under this embedding operation each quartet of trace subsets O 2m−1 , E 2m , O 2m , E 2m+1 undergoes permutation, with probabilities determined by p. We will not repeat that analysis, since it can be found in much of the other steganography literature including [2,3,5].…”
Section: Derivation Of Likelihood Functionmentioning
confidence: 99%
“…We also consider a new and more general problem, mixing wet papers (locked positions) [10] and simple syndrome coding (low number of changes) [11] in order to face not only passive but also active wardens. However, the implementation of Steganographic scheme is delayed by the complexity of Guruswami-Sudan list decoding, although offering an adaptive compromise between the number of locked positions and the number of changes.…”
Section: New Steganographic Scheme Based On Reed-solomon Codesmentioning
confidence: 99%